Исследование зависимости диэлектрической проницаемости компонентов бензинов от их антидетонационной стойкости - Григоров, Андрей Борисович (НТУ "ХПИ", 2007)
Пропонується діелектричний метод визначення антидетонаційної стійкості компонентів бензину. Цей метод дозволяє здійснювати безперервний контроль їхньої якості у процесі виробництва. За допомогою регресійного аналізу автором здійснений опис залежності між антидетонаційною стійкістю та діелектричною проникністю.

The dielectric method of the antidetonation stability of components of petrol is offered. This method allows to carry out the continuous control of their quality during manufacturing process. By means of the regression analysis the dependence between the antidetonation stability and dielectric permeability is described by the author.
Keywords: карбюраторные двигатели; детонация; товарные бензины; углеводородные компоненты; октановое число; рафинат; катализат